The relationship between Arabic language study and band score gain on APT - Omar, Zakaria; Kheir, Abdalla Mohamed Adam; Abdullah, Rahmat (2017)
This research is aimed at investigating the relationship between intensive Arabic language study (course) and band score gains on the APT (Arabic Placement Test). It investigates the progress of the participating students from non-native speakers of Arabic enrolled in Arabic language course at CELPAD (Centre for Languages and Pre-Academic Development), IIUM. Using APT test results obtained by the participating students at the entrance of IIUM and after a completion of a semester of intensive Arabic language study, the research investigates patterns of improvement among the participating students. The research also used questionaires and interviews to investigate the rate and nature of the improvement, as well as the educational, personal and social factors influencing this improvement. Interviews also be conducted with the teachers in order to elicit information about the learning environment and the factors they see as critical in determining the progress of the students in general. Key findings included the following points: (1) The results revealed that students made variable progress in Arabic during 14 weeks of study with an average gain of about two bands overall. (2) The average improvement on Writing (average of three bands) was higher than the average improvement on Reading (average of one band). (3) Students with lower initial results in Writing tended to improve significantly more than students with higher results. (4) The students need more exercises and strategies to answer various types of question in APT.